Eating disorders, energy intake, training volume, and menstrual function in high-level modern rhythmic gymnasts - Sundgot-Borgen, J. (International Journal of Sport Nutrition and Exercise Metabolism, 1996)
This study examined clinical and subclinical eating disorders (EDs) in young Norwegian modern rhythmic gymnasts. Subjects were 12 members of the national team, age 13-20 years, and individually matched nonathletic controls. All subjects participated in a structured clinical interview for EDs, medical examination, and dietary analysis. Two of the gymnasts met the DSM-III-R criteria for anorexia nervosa, and 2 met the criteria for anorexia athletica (a subclinical ED). All the gymnasts were dieting in spite of the fact that they were all extremely lean. The avoidance of maturity, menstrual irregularities, energy deficit, high training volume, and high frequency of injuries were common features among the gymnasts. Ther is a need to learn more about risk factors and the etiology of EDs in different sports. Coaches, parents, and athletes need more information about principles of proper nutrition and methods to achieve ideal body composition for optional health and athletic performance.